Jejunojejunal intussusception caused by a jejunal lipoma in a 92-year old patient: CT diagnosis - Obilat, Samia; Harras, Yahya El; Lasri, Lina; Imrani, Kaoutar; Nassar, Ittimade (International Journal of Research in Medical Sciences, 2026)
Adult intussusception is an uncommon cause of bowel obstruction and is usually associated with an identifiable pathological lead point. Among benign etiologies, submucosal lipomas of the small bowel are rare but may induce intussusception when they reach a significant size. We report the case of a 92-year-old man who presented with acute abdominal pain and subocclusive syndrome. Because of his history of bilateral inguinal hernias, strangulated hernia was initially suspected. Contrast-enhanced CT instead demonstrated an uncomplicated jejunojejunal intussusception caused by a 46-mm submucosal jejunal lipoma, with no evidence of bowel ischemia. Conservative management resulted in a favorable clinical outcome. This case highlights the pivotal role of CT in establishing the diagnosis, identifying the benign lead point, excluding ischemic complications, and guiding appropriate management in elderly patients presenting with acute abdominal pain.